IMPLEMENTASI PERATURAN MENTERI KELAUTAN DAN PERIKANAN REPUBLIK INDONESIA NOMOR PER. 19/MEN/2010 Tentang Pengendalian Sistem Jaminan Mutu dan Keamanan Hasil Perikanan (Studi Mengenai Pelaksanaan Pemberian Sertifikat Ekspor Ikan Di Balai Karantina Kelas I - Ilmu Flikhah, Anis Rosana (JPAP: Jurnal Penelitian Administrasi Publik, 2016)
Certification of fish exports carried out in order to ensure that fish or fishery products were produce from the territory of the Republic of Indonesia free of pest quarantine fish or illness that required, according to the type and amount with the accompanying documents as well as free or do not have the potential as a medium for disease be transmitted to humans. The purpose of this research is to analyze and describe the fish export certification services in Class I Fish Quarantine Surabaya, and to describe the positive impact gained the certification of exports of fish in Fish Quarantine Class I Surabaya. Analysis data techniques used in this research is descriptive qualitative data analysis techniques. The results showed that: a) fish export certification services in Class I Fish Quarantine Surabaya basically been carried out in accordance with the existing procedures that provide fast service, precise, inexpensive, safe, fair and accountable. However, there is a shortage of human resources side, there are the employees or less service personnel to be friendly to the public while giving fish export certification services; and b) The positive impact of obtaining export fish certification in Fish Quarantine Class I Surabaya are fish exporter obtained evidence that fish to be exported has met the requirements and declared free of the pest, quarantine fish or illness that required, so that the process of fish export activities can to do. Keywords: Implementation, Fish Export Certificates, Certification Service.